2012
DOI: 10.1128/mbio.00409-12
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Peptidoglycan Modifications Confer Lysozyme Resistance and Contribute to Survival in the Host

Abstract: The prominent host muramidase lysozyme cleaves bacterial peptidoglycan (PG), and the enzyme is abundant in mucosal secretions. The lytic enzyme susceptibility of Gram-negative bacteria and mechanisms they use to thwart lytic enzyme activity are poorly studied. We previously characterized a Helicobacter pylori PG modification enzyme, an N-deacetylase (PgdA) involved in lysozyme resistance. In this study, another PG modification enzyme, a putative PG O-acetyltransferase (PatA), was identified. Mass spectral anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 40 publications
3
63
1
Order By: Relevance
“…Recently, our laboratory demonstrated that H. pylori apo-AcnB binds to the 3= UTR of the peptidoglycan deacetylase (pgdA) transcript, resulting in transcript stability and increased PgdA expression (5). PgdA confers lysozyme resistance and immune evasion; its expression is increased when H. pylori cells are exposed to oxidative stress or are in contact with host immune cells (19)(20)(21)(22). AcnB plays an important role in the posttranscriptional regulation of PgdA (5).…”
mentioning
confidence: 99%
“…Recently, our laboratory demonstrated that H. pylori apo-AcnB binds to the 3= UTR of the peptidoglycan deacetylase (pgdA) transcript, resulting in transcript stability and increased PgdA expression (5). PgdA confers lysozyme resistance and immune evasion; its expression is increased when H. pylori cells are exposed to oxidative stress or are in contact with host immune cells (19)(20)(21)(22). AcnB plays an important role in the posttranscriptional regulation of PgdA (5).…”
mentioning
confidence: 99%
“…H. pylori can thrive in the gastric mucosa by employing a battery of diverse antioxidant enzymes that detoxify oxidants and repair essential biomolecules (2,3). Additionally, H. pylori utilizes other mechanisms to persist in the host, including peptidoglycan (PG) modification (4).…”
mentioning
confidence: 99%
“…6D). These lysozyme killing experiments were performed in the presence of human apolactoferrin, another important component of airway fluids (102) that can increase the sensitivity of Gram-negative bacteria to killing by lysozyme (47,72,103) by affecting the permeability of the outer membrane (74). Among the 12 M. catarrhalis strains whose genomes have been sequenced (35,36), LipA proteins have 99 to 100% identity, with LipB proteins being 97 to 100% identical.…”
Section: Discussionmentioning
confidence: 99%